Valuasi ekonomi pohon tua sebagai pembentuk karakter lanskap perkotaan Malang: Pendekatan metode Danish (VAT03) - Medha Baskara; Ahmad Zahid Izulhaq (Jurnal Arsitektur Lansekap, 2026)
Old urban trees are vital environmental and identity assets currently threatened by urbanization and infrastructure development. The lack of protection policies based on economic valuation poses a significant challenge to the conservation of these historic trees. This study aims to estimate the economic value of three types of old trees (Samanea saman, Ficus benjamina, and Canarium indicum) in Malang City using the Danish Valuation Method (VAT03). The assessment is based on four parameters: Basic Value (B), Health Factor (H), Location Factor (L), and Age Factor (A). Data were collected through field observations at Tugu Square, Merdeka Square, and Panglima Sudirman Street, complemented by literature data from the Bouwplan I area. The results indicate that the Kenari tree (C. indicum) possesses the highest average economic value at IDR 577,355,787.31. This high valuation is driven by its basic value, long life expectancy, and architectural historical significance. This study emphasizes the need to integrate economic tree valuation into urban spatial planning policies to strengthen the conservation of old urban trees.